Socioeconomic and urban-rural differentials in exposure to air pollution and mortality burden in England - Ai Milojevic; Claire L. Niedzwiedz; Jamie Pearce; James Milner; Ian A. MacKenzie; Ruth M. Doherty; Paul Wilkinson (BMC, 2017)
Abstract Background Socioeconomically disadvantaged populations often have higher exposures to particulate air pollution, which can be expected to contribute to differentials in life expectancy. We examined socioeconomic differentials in exposure and air pollution-related mortality relating to larger scale (5 km resolution) variations in background concentrations of selected pollutants across England. Methods Ozone and particulate matter (sub-divided into PM10, PM2.5, PM2.5-10, primary, nitrate and sulphate PM2.5) were simulated at 5 km horizontal resolution using an atmospheric chemistry transport model (EMEP4UK). Annual mean concentrations of these pollutants were assigned to all 1,202,578 residential postcodes in England, which were classified by urban-rural status and socioeconomic deprivation based on the income and employment domains of the 2010 English Index of Multiple Deprivation for the Lower-level Super Output Area of residence. We used life table methods to estimate PM2.5-attributable life years (LYs) lost in both relative and absolute terms. Results Concentrations of the most particulate fractions, but not of nitrate PM2.5 or ozone, were modestly higher in areas of greater socioeconomic deprivation. Relationships between pollution level and socioeconomic deprivation were non-linear and varied by urban-rural status. The pattern of PM2.5 concentrations made only a small contribution to the steep socioeconomic gradient in LYs lost due to PM2.5 per 103 population, which primarily was driven by the steep socioeconomic gradient in underlying mortality rates. In rural areas, the absolute burden of air pollution-related LYs lost was lowest in the most deprived deciles. Conclusions Air pollution shows modest socioeconomic patterning at 5 km resolution in England, but absolute attributable mortality burdens are strongly related to area-level deprivation because of underlying mortality rates. Measures that cause a general reduction in background concentrations of air pollution may modestly help narrow socioeconomic differences in health.